Data recommendation engine for a web–based research community social network platform - Tay, Wee Meng (2019)
Social media platforms have gained a large amount of attention as there are many social media applications available for people to use. Some of the social media applications available includes WhatsApp, YouTube, Facebook, Instagram, Twitter, LinkedIn and many others. Based on the statistics of social network penetration in Singapore as of the third quarter of 2017, the top five social media applications are WhatsApp (73%), YouTube (71%), Facebook (70%), Instagram (44%) and Facebook Messenger (42%) (Statista, 2018).